Departmental Heads’ perspective on collaborative strategies to enhance teamwork in secondary schools at Nketoana District - Koloti, Machogoane Sanah (University of the Free State, 2023)
There are many situations in a school environment that need to be viewed to form effective teamwork at school. The literature confirms that teamwork is an important tool in any organisation, such as schools, which should practice teamwork to achieve the vision and goals they have set to be functional. Collaborative strategies should, therefore, be in place to ensure that teamwork is effective. Therefore, managers and leaders in schools, especially Departmental Heads, are entrusted with ensuring that collaborative teamwork is practiced effectively in schools for improved learner academic success. However, teamwork in schools still proves to be a challenging concept. Lack of teamwork in schools is believed to be one of the factors that are detrimental to the success and efficiency of the core business of schools, which is teaching and learning. This study aimed to explore collaborative strategies that can enhance teamwork in secondary schools. The study was grounded by the collaborative theory used as a lens for the study. The study employed a qualitative research approach to gather data through a case study research design. Semi-structured interviews, document analysis, and focus group discussions were adopted as data collection instruments. Purposive sampling was employed to sample 12 Departmental Heads (DH) from three schools in one Department of Education district in the Free State Province. Content analysis was used to analyse data where four themes emerged from the perceptions and expressions of the participants. The findings revealed that collaborative strategies are a tool that can assist in enhancing teamwork in secondary schools. The findings further revealed that Departmental Heads implement various collaborative strategies such as class subject meetings, school twinning, analysing and accounting for the results together, team planning and teaching, team marking, and parental involvement, to enhance teamwork in secondary schools. However, the findings also revealed that the Departmentl Heads do experience some challenges with the collaborative strategies they employ to enhance teamwork but find ways to mitigate the challenges. The study, therefore, recommends that every stakeholder in schools play a role in ensuring that more effective collaborative strategies to enhance teamwork are implemented in schools.
Dissertation (M.Ed.(Higher Education Studies))--University of the Free State, 2023
Keywords: Teamwork; Secondary schools; Departmental heads; Collaborative strategy